Current Management of Fluorometholone Steroids in Pediatric Vernal Conjunctivitis: A Literature Review - Fajar, Muhammad Fauzi; Siallagan, Maria; Nabighah, Gladis Salsabila Najla; Wijaya, Pande I Gede Indra; Anugrahsari, Santi (Jurnal MedScientiae, 2024)
Vernal conjunctivitis is a rare allergic eye disease, usually affecting children in the prepubertal years and can last between 5 to 10 years. Treatment of this condition is often challenging, requiring effective therapies to reduce symptoms. This literature review, conducted between 2015 and 2023, aimed to evaluate the effectiveness of fluorometholone steroid use in the treatment of pediatric vernal conjunctivitis. Recent studies comparing the effectiveness of Fluorometholone 0.1% in the treatment of Vernal Keratoconjunctivitis (VKC) were analyzed. The results showed that Fluorometholone was effective compared to Cyclosporine in reducing VKC symptoms. However, the use of Fluorometholone should be done with caution due to potential side effects such as increased intraocular pressure and risk of infection.Fluorometholone is an effective treatment option for vernal conjunctivitis in children. However, it is important to have close monitoring by an ophthalmologist to avoid serious side effects. With careful monitoring and proper dose adjustment, Fluorometholone can be a safe and effective therapy in managing this condition.